Porous graphdiyne loading CoOx quantum dots for fixation nitrogen reaction. (November 2021) - Liu, Yuxin; Xue, Yurui; Hui, Lan; Yu, Huidi; Fang, Yan; He, Feng; Li, Yuliang
Abstract: Over the years, scientists have sought to pursue ammonia (NH3 ) production, and have tried to bring huge transform and benefits for renewable energy technologies to replace high-pollution and energy-consuming Haber-Bosh processes. Here we would like to launch a novel catalyst of porous graphdiyne (GDY) based quantum dots for ammonia production. The ultra-high catalytic performance is origin from the rapid conversion of valence states of metal element within the catalyst and the great enhancement of surface plasmon resonance (SPR). This highly compatible synergistic effect enables excellent photocatalytic performance. After 46 independent experiments, a highest NH3 yield rate (YNH3 ) of 26502 μmolNH3 gcat. −1 h −1, a lowest YNH3 of 15026 μmolNH3 gcat. −1 h −1, and an average YNH3 of 19583 μmolNH3 gcat. −1 h −1 in 46 independent experiments were respectively given, as well as the high long-term stability. Graphical Abstract: A novel catalyst of porous graphdiyne (GDY) based quantum dots was precisely synthesized for photocatalyzed ammonia production. The strong advantages of graphdiyne could effectively regulate photocatalytic activity and coordination environments and great enhance the surface plasmon resonance (SPR) effect, which enables excellent NH3 yield rate and high long-term stability. ga1 Highlights: A novel catalyst of porous graphdiyne based quantum dots was precisely synthesized for photocatalyzed ammonia production. Graphdiyne effectively regulates the coordination environments and the surface plasmon resonance effect of the catalysts. The unique properties of the catalyst endow it with excellent NH3 yield rate and high long-term stability.